(untitled) (Bangladesh Journal of Plant Taxonomy, 2012)
Nineteen new combinations and one new name are proposed in Breynia for taxa previously treated in Sauropus. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13125 Bangladesh J. Plant Taxon. 19(2): 119-122, 2012 (December)